The Understanding of Positive Thinking - Yahaya, Azizi (2008)
Happiness, joy, health and a successful outcome in all action or situation are all about how if we believed something, we could make it happen. Surprise, calmness, relaxation and correct posture are the four basic principles in positive mind that we can make useful in our lives. The power of positive mind is a mighty power that is always shaping our lives. Our mind can create everything if we know how to use and conduct it. We can reach whatever level we can with a positine mind.